La protection du consommateur à l'épreuve des technologies de l'information et de la communication : étude du droit ivoirien à la lumière du droit français - Alleme, Apo (Université de Perpignan Via Domitia, 2019)
Les technologies de l’information et de la communication (TIC) qui recouvrent l’ensemble des outils et techniques résultant de la convergence des télécommunications ont révolutionné les comportements et les habitudes des consommateurs. Si ces technologies ne se limitent pas au réseau internet c’est la montée d’internet qui a renouvelé la problématique de la protection du consommateur. En réponse, le législateur ivoirien a, à travers la loi de 2016 relative à la consommation, essayé de s’arrimer aux standards internationaux relatifs à la protection du consommateur. Le nouveau dispositif adopté s’ajoute au droit positif ivoirien et au cadre législatif communautaire (UEMOA et CEDEAO). Cependant, le système se révèle insuffisant et, à certains égards, inadapté à la protection du consommateur, notamment dans l’hypothèse d’une vente conclue par le canal des TIC. Ces insuffisances s’observent au moment de la formation et de l’exécution du contrat de vente. Dans ce contexte, le cadre législatif français qui étend ses sources dans le droit communautaire européen peut, à bien d’égards, inspirer le législateur ivoirien. Il ne s’agit pas de transposer intégralement ce système en droit ivoirien. En effet, à l’épreuve des TIC, la protection du consommateur passe par la recherche de nouveaux points d’équilibre entre le consommateur et le professionnel. Information and communication technologies (ICTs), which encompass all the tools and techniques resulting from the convergence of telecommunications, have revolutionized the behavior and habits of consumers. These technologies are not limited to the Internet, the rise of which has renewed the problem of consumer protection. In response, the Ivorian legislator, through the 2016 law on consumption, tried to be consistent with international standards relating to consumer protection. The new mechanism adopted is in addition to current Ivorian law and the Community legislative framework (UEMOA and ECOWAS). However, the system is proving insufficient and, in some respects, unsuitable for consumer protection, especially in the event of a sale through the ICT channel. These deficiencies occur at the time of the formation and enforcement of the sales contract. In this context, the French legislative framework that extends its sources in European Community law can, in many ways, inspire the Ivorian legislator. It does not entail the total transposition of the French system into the Ivorian law. Actually, with the new challenges of ICTs, the protection of the consumer can only be guaranteed by the search for equilibrium between the consumer and the professional.
Keywords: Commerce électronique; Consommateur; Consommateur (protection); Consumer; Côte d'Ivoire; E-commerce; Electronic payment; France; GDPR; Paiement électronique; Personal data protection; Protection des données personnelles; RGPD; Études comparatives

Les opérations de regroupement de l'endettement du consommateur - Sawadogo, Rélouindé Béatrice (Université Clermont Auvergne‎, 2019)
Le crédit de regroupement destiné aux ménages et aux particuliers fait aujourd’hui partie intégrante des crédits régis par le code de la consommation. Dans un contexte de multi-endettement le plus souvent inadapté à la situation financière des débiteurs, le recours au regroupement de crédits s’inscrit dans la recherche de solutions par le débiteur pour résorber son malendettement ou mieux gérer son budget. Favorisée entre autres par la baisse des taux d’intérêt, l’offre de crédit de regroupement tend à devenir un outil de conquête de parts de marché. Demeuré longtemps sans encadrement précis, le regroupement de crédits bénéficie désormais d’un cadre strict et contraignant initié par la loi n°2010-737 du 1er juillet 2010 portant réforme du crédit à la consommation. Un encadrement dont la substance porte sur la définition des régimes des opérations de regroupement et leurs conditions de formation très formalistes et de nature consumériste. Cela traduit des avancées innovantes en la matière mais cette règlementation tient insuffisamment compte des spécificités du regroupement d’où la nécessité d’évoluer vers un cadre juridique spécifique plus approprié. Il est en effet nécessaire d’intégrer dans l’encadrement du regroupement la définition de l’opération, son procédé de mise en œuvre et d’autres aspects tenant au processus de restructuration. Ce qui permettra de définir des droits et des devoirs pour les parties prenantes aux crédits regroupés et de mieux tenir compte de la fragilité du consommateur-emprunteur par des mesures de prévention d’un nouvel engrenage dans l’endettement excessif. Le mécanisme du regroupement étant néanmoins susceptible de résorber efficacement le malendettement, il pourrait être utilisé comme mesure de traitement du malendettement dans le cadre des procédures de désendettement. Cela nécessite la définition de conditions d’ouverture du droit du surendettement aux situations de malendettement et de trouver des sources de financement du réaménagement de l’endettement via le crédit de regroupement que proposerait la Commission de surendettement. A propos, se tourner vers l’un des créanciers prêteurs est préconisé, mais il faudrait envisager la mise en place d’un fonds public spécifique de soutien aux particuliers qui financerait subsidiairement ledit crédit en cas d’exercice par le banquier de sa liberté de refuser le crédit. In fine, même si les différentes mesures de traitement du malendettement et du surendettement sont utiles, il est nécessaire et primordial de trouver de meilleurs outils pour les prévenir. The Consolidation of Debts to households and individual customers is now part of the Credit Offer regulated by the French Consumption Code Law.In the framework of multiple debts unfit to the financial situation of the Debtors, the use of debts consolidation is geared towards the search of solutions by Debtors to solve bad debts or better manage their budget. Favored by the decrease of interest rates, the consolidation of debts has evolved as a tool to gain additional market shares. Long Time without any structured monitoring, the consolidation of debts is now structured in a strict and binding framework initiated by the law n°2010-737 of July 2010 amending the consumption debt Law. A framework which is grounded on defining the different types of debts consolidation and the conditions of their creation – This process being very formal and of consumerist type. This entails innovative progress in this area field, but these rules do not take into account the peculiarities of debts consolidation, thus, implying the necessity to evolve towards a more specific legal framework. It is now compulsory to integrate within the framing of Debts Consolidation, the definition of the nature of these operations, their methods of implementation and additional aspects related to the restructuring process. This will allow to define the rights and obligations of the stakeholders to debts Consolidation and take into account the fragility of the consumer-borrower through prevention measures against the threat of falling back into the traps of excessive debts. The mechanisms of debts consolidation is however a potential way to solve excessive debts, it could be used as a healing measure to treat excessive Debts in the framework of deleveraging processes. For that purpose, leveraging one of the creditors can be advocated, but one should also contemplate the setup of a Public Fund to support individual customers, and that would finance alternatively such a credit, if not accepted by the bank.In fine, even though the different treatment measures against excessive and bad debts are useful, it is highly important to find out better tools to prevent those situations.
Keywords: Bad debt; Borrower; Consommateur (protection); Consumer; Consumer protection; Contractual freedom; Credit; Crédit; Crédit de substitution; Debts consolidation; Débiteur et créancier; Emprunteur; Fonds spécifique; France; Information spécifique; Legal framework; Lender; Liable credit; Liberté contractuelle; Malendettement; Multi-debt; Multi-endettement; Prêt responsable; Prêteur; Prêts personnels; Re-negotiation; Reframing; process; Regroupement de crédits; Renégociation; Restructuration; procédé; Risk of excessive debt; Risque de surendettement; Régime juridique; Specific fund; Specific information; Substitution credit; Surendettement

Resale price maintenance in consumer good markets: an economic justification for the prohibition of RPM - Schwaderer, Melanie Ariane (European University Institute, 2019)
The thesis contributes to the debate on the EU’s approach to the business practice of resale price maintenance (RPM), which is widely criticized as too strict and in conflict with what is considered to be the consensus in the economic literature. The thesis critically dissects the economic consensus, on which the critique against the EU’s approach is based, by analyzing the empirical evidence that is cited to support the claim that RPM can frequently be explained by the service-based RPM models and shows that there is no convincing evidence that would support the significance of these positive RPM models that predict positive effects on welfare. To support this finding the thesis collects new evidence by surveying the marketing literature and shows that not only is there no convincing evidence that the positive RPM models frequently apply, but to the contrary there is evidence that these models are inconsistent with the real world phenomenon of RPM. Having refuted the service-based models the thesis takes up the scientific challenge that “it takes a theory to beat a theory” and proposes to fill the gap with three price-based models. The thesis offers an analysis of the three price-based RPM models, first from the perspective of welfare effects and then from a broader economic perspective in an attempt to ultimately show that the EU approach to RPM can be justified based on these economic models. All three models explain the situation in which RPM is used by a branded good manufacturer to create the perception of high quality, which is used either as a credible quality signal, becomes a component of the product or is used to bias the consumer decision; they thus enter the difficult terrain of consumer preference formation and of markets for the intangible components of a product.
Keywords: Competencia; Competition law; European Union countries; Marketing; Price maintenance

Droit de la consommation et régime de l'obligation : essai de construction d’un régime de l’obligation consumériste au travers de l’exemple de la prescription - Calcio Gaudino, Mathilde (Université de Lorraine, 2018)
Cette thèse aborde la question du régime de l’obligation consumériste au travers de l’exemple de la prescription. Elle s’intéresse à la réception par le droit de la consommation, droit par essence inégalitaire, de la prescription en tant que mécanisme du régime général de l’obligation. Le délai biennal de l'action en paiement du professionnel peut-il être interrompu ? Quels sont les effets des pourparlers sur le court délai de l'action en inexécution du consommateur ? Comment s'impute le paiement d'une dette prescrite en droit de la consommation ? Ce travail s'attache à démontrer l'inadéquation du recours au régime de droit commun dans les rapports consuméristes, mais aussi les conséquences dommageables des solutions actuelles apportées par le droit de la consommation. Il se propose d'étudier, par une analyse systématique et détaillée de la jurisprudence du fond et de la Cour de cassation, le traitement de la prescription dans les contrats de consommation classiques, et dans les contrats de consommation inversés. Il s’intéresse également à la prescription des actions en nullité et en répétition de l’indu. L'étude de la jurisprudence accessible et du précontentieux disponible révèle que le consommateur est pénalisé à deux égards :– l'application des mécanismes de droit commun (computation, interruption, suspension, interversion des délais et prescription présomptive de paiement) confère en réalité au professionnel la maîtrise des délais, que celui-ci agisse en qualité de créancier ou de débiteur ;– la coexistence de plusieurs délais de nature et de régime différents (prescription, prescription présomptive et forclusion) est source de confusion tant pour les parties que pour les juridictions. La comparaison des courants jurisprudentiels des cours d'appel dans le contentieux de masse met en relief des pratiques opposées qui, outre l'enjeu économique important pour le consommateur, privent celui-ci d'un accès égal à la justice.La démonstration des déséquilibres induits par le régime de la prescription s’accompagne de pistes de réflexions prospectives. Théorisant les pratiques actuelles, l'étude sert de base à la construction d'un modèle raisonné de prescription de l'obligation consumériste et de son régime, fondé sur le traitement différencié des parties
Keywords: BtoC relationships; Commencement date; Consommateur (protection); Consumer Law; Contentieux de masse; Droit de la consommation; Déchéance (droit); Forclusion; French Law; Mass litigations; Obligation; Obligations (droit); Prescription; Prescription (droit); Suspension

The realisation of rights in terms of the Consumer Protection Act 68 of 2008 - Scott, Tshepiso (University of South Africa, 2018)
The thesis examines the enforcement of consumer rights in South Africa, and is set against the backdrop of the underlying principles and theories on the enforcement of consumer protection law. It then analyses the various forms of consumer protection law enforcement mechanisms that were in place prior to the implementation of the Consumer Protection Act 68 of 2008, and sets out why there was a need for the enactment of the Consumer Protection Act. The thesis then critically discusses the consumer protection law enforcement mechanisms introduced and/or catered for by the Consumer Protection Act. The in-depth comparative analysis against the consumer protection law enforcement dispensations in both India and the United Kingdom culminates in a critical analysis of the successes and shortcomings of consumer protection law enforcement regime in present-day South Africa; as well as recommendations (in the form of legislative amendments and practical solutions) on how the South African consumer protection enforcement framework can be improved in order to facilitate the realisation of consumer rights.
Keywords: Consumer protection; Consumer rights; Enforcement mechanisms

Le droit de mettre fin à la relation contractuelle de distribution - Wang, Juanrong (Université de Lille, 2018)
Le droit de mettre fin à une relation contractuelle comprend deux aspects : le droit de résilier un contrat à durée indéterminée et le droit de refuser de renouveler un contrat à durée déterminée. Son existence est incontestable à l’égard de l’ensemble des contrats de distribution, y compris ceux qui revêtent la qualification de mandat. Néanmoins, son exercice est encadré par la théorie de l’abus lorsque le titulaire de ce droit subjectif manque à un devoir moral du maintien temporaire de la relation contractuelle. Dans cette hypothèse, laresponsabilité civile du titulaire du droit est engagée sur le fondement de la notion de faute.Toutefois, ce même titulaire peut être contraint de payer une indemnité même en absence de toute faute commise de sa part : telle est l’hypothèse de l’indemnité de fin de contrat prévue au bénéfice d’une partie des distributeurs. Cependant, il ne faut pas interpréter cette indemnité comme une remise en cause de ce droit subjectif. En effet, cette indemnité trouve sa justification dans les éléments étrangers à ce droit. En d’autres termes, le paradoxe entre l’indemnité et le droit subjectif n’est qu’apparent : le droit de mettre fin à une relation contractuelle de distribution est dépassée par l’indemnité de fin de contrat.
Keywords: Circuits de distribution; Contract; Contrats; Distribution agreement; Droit de la distribution; Droit des contrats; Droit subjectif; Indemnité; Résolution de contrat

Strict product liability in South Africa : an analysis of the concept of "defect" and the statutory defences available to the supply chain - Tennant, Sarah-lynn (University of Pretoria, 2018)
Defective products cause harm to persons and property on a daily basis. Product Liability law has accordingly evolved as a specialised area of the law of delict which seeks to prevent product accidents from happening and provides compensation in the event that defective products nevertheless reach the consumer market. Accordingly product liability regimes generally have both ex ante components such as product standards, recall mechanisms and liability provisions which are aimed at deterrence and risk-spreading as well as provisions that are applied ex post to provide redress and compensation. Designing an appropriate legal framework to underpin a product liability regime is a daunting task that involves achieving of an appropriate balance between the interests of various parties inter alia those of consumers, suppliers and the broader community. In recent decades many countries have migrated from a fault-based product liability regime to a regime which purportedly imposes strict liability on the whole supply chain. This bold move in modern product liability was pioneered in the United States who has since returned to fault-based liability for design and warning defects whilst returning strict liability in respect of manufacturing defects. After many years South Africa has joined the group of countries that applies strict liability to all defects regardless of their type. Notably the product liability regime introduced into South African law by means of the Consumer Protection Act 68 of 2008 (“CPA”) resembles the main features of the EU Product Liability Directive 85/374/EEC. The EU Model has also been taken over by Australia when they transitioned to a purportedly strict product regime in 1992. During this process the thesis also considers whether, by adopting the European model, South Africa has taken over a model which has been criticised by some American authors as outdated and based on 1965 strict product liability rhetoric as contained in section 402A of the Restatement (Second) of Torts which approach has since been discarded in the US in favour of the hybrid approach contained in the US Restatement (Third): Product Liability. This thesis focuses on product liability ex delicto. Its main aim is to interrogate and evaluate the product liability provisions contained in section 61 of the CPA, specifically with regard to the pivotal concept of defect and the statutory defences the Act has introduced. It details South Africa’s journey from the fault-based common law of product liability to the purportedly strict regime espoused by the CPA, which regimes operate parallel to each other. This is done to facilitate an understanding of the differences between the two regimes and specifically to aid interpretation and application of the product liability provisions in the CPA that deal with defectiveness and the new statutory defences. In order to obtain further guidance on how the concept of “defect” and the statutory defences in the CPA should, or could, be interpreted and applied the thesis initially considers the general foundational principles underlying product liability law and how this area of law has evolved in the United States, being the origin of modern product liability law. However, given that the South African regime of “strict” product liability ex delicto has its roots in the EU Directive and resembles some of the adapted features of the Australian product liability regime contained in the comprehensive Australian Consumer Law, the main comparative focus is on these two jurisdictions.
URI: https://repository.up.ac.za/handle/2263/70768
Keywords: Defective product; Product liability; South Africa; Supply chain

Le non-professionnel et le petit professionnel : la protection de deux contractants faibles par le droit privé - Haba, Parfait (Université Paris 10, 2017)
Pendant longtemps, le non-professionnel a été considéré comme un professionnel dont la situation de faiblesse était comparable à celle du consommateur et il était protégé comme tel. Or, le juge européen a défini le consommateur comme « visant exclusivement la personne physique ». Cela a conduit le juge français à nuancer sa position ; le non-professionnel est défini comme la personne morale n’exerçant pas d’activité professionnelle. De son côté, la notion de petit professionnel a été consacrée par les textes relatifs au droit de la consommation et au droit de la concurrence. Si ces contractants faibles sont protégés c’est avant tout parce qu’ils peuvent être marqués par une situation de faible économique, technique ou juridique. En tout état de cause la protection n’est accordée que par détermination de la loi et elle doit rester circonstanciée. Dans tous les cas, la protection de ces contractants est spécifiée par l’absence de standardisation car elle ne peut être calquée sur le modèle de protection du consommateur. Partant, la protection de ces contractants faibles est nécessaire contre les abus contractuels. Ainsi, le non-professionnel est essentiellement protégé contre les clauses abusives par l’appréciation du déséquilibre significatif dans les contrats de consommation. Alors que le petit professionnel est protégé par le contrôle du contenu du contrat et surtout contre toutes sortes d’abus dans les pratiques anticoncurrentielles. Aussi, les mécanismes de l’information prévus par le droit de la consommation, le Code civil ou ceux prévus au profit de l’acquéreur non-professionnel ou des non-avertis peuvent être étendus au profit du non-professionnel et du petit professionnel.
Keywords: Anticompetitive practice; Catégories socio-professionnelles; Clauses abusives; Competencia; Concurrence; Consommateur; Consommateur (protection); Consumer; Contractant faible; Contractual equilibrium; Contrat de dépendance; Dependency contract; Déséquilibre significatif; Equilibre contractuel; France; Non-professional; Non-professionnel; Petit professionnel; Pratique anticoncurrentielle; Significant imbalance; Small business; Unfair terms; Weak contractor; Équilibre contractuel

Droit de la construction et droit de la consommation : Essai sur les critères de qualification des contractants - Seigle-Ferrand, Orianne (Université de Montpellier, 2017)
Lors d’une opération immobilière de construction, deux ensembles de règles, qui sont le droit de la construction et le droit de la consommation, viennent se superposer pour apporter un certain niveau de protection lorsque l’acquéreur ou le maître de l’ouvrage est un consommateur ou un non-professionnel. Corrélativement, ils génèrent de nombreuses obligations mises à la charge des professionnels. Ce projet de recherche a donc pour finalité de réaliser, d’une part, un état des lieux des différentes problématiques de protection nées de l’application cumulative de ces deux branches du droit et, d’autre part, de proposer des solutions de règlement en cas de « conflit ». En effet, si les conséquences positives d’une telle combinaison sont indéniables, cette étude ne serait pas complète si l’on n’envisageait également les effets pervers que cette double protection peuvent engendrer dans la pratique au regard de l’économie du contrat, du secteur du bâtiment et de l’esprit qui anime le droit de la construction de manière plus générale. L’objectif poursuivi étant de rendre le droit plus efficace pour sécuriser, autant que possible, l’opération de construction, pour l’ensemble des acteurs du secteur : tant professionnels, pour qu’ils prennent la mesure de leurs responsabilités et obligations (entrepreneurs, promoteurs, architectes, banquiers, notaires…) que pour le « consommateur immobilier » : accédant ou maître d’ouvrage, qui doit pouvoir avoir une vision, la plus claire possible, des contrats qui lui sont soumis afin que sonconsentement soit réellement éclairé.
Keywords: Building sector; Consommateur (protection); Consommateur immobilier; Construction; Consumer real estate; Harmonization - balance of contract; Housing; Interactions (law); Logement; Promotion immobilière – Droit; Protections - obligations (law)

La protection pénale du consentement donné par le consommateur - Aznar, Thibaut (Université de Perpignan, 2017)
La protection pénale du consommateur est un enjeu essentiel, à plus forte raison, à la suite des dernières réformes législatives intervenues en la matière. La protection du consentement du consommateur représente l'essence même de l'intervention du droit pénal dans la sphère consumériste. La question fondamentale qu'il convient de se poser est donc celle de savoir si ce droit pénal sanctionne les comportements délictueux dont peut faire preuve le professionnel de manière accessoire au droit civil ou bien, plus intéressant, s'il revêt une autonomie dans la protection du consentement du consommateur, sans être un simple droit sanctionnant et dissuasif.
Keywords: Business practice; Consentement libre; Consentement éclairé; Consommateur; Consommateur (protection); Consumer; Criminal protection; Criminal sanction's efficency; Droit pénal (droit européen); Efficacité des sanctions pénales; Free character of consent; Informed character of consent; Pratiques commerciales

Redes contratuais com função de distribuição - Drews, Rafael Induzzi (Universidade de São Paulo, 2017)
A presente tese versa sobre redes contratuais com função de distribuição, assim entendidas aquelas formadas por contratos de distribuição, concessão comercial - regidos pela Lei 6.729/79 - e franquia. Nessas redes, o organizador ou líder (fornecedor, fabricante ou franqueador) mantém contratos bilaterais homogêneos com cada um dos distribuidores, concessionários e franqueados, os quais, por sua vez, não mantêm relação contratual formal entre si. Ao líder são reservadas diversas prerrogativas contratuais que lhe possibilitem organizar e controlar o funcionamento da rede, com vistas a uma maior eficiência global e ao fortalecimento da marca. O trabalho procura definir essas redes e compreender como o direito, em especial o direito contratual, deve tratá-las. Sustenta-se que elas não se esgotam nos contratos bilaterais que as formam, sendo dotadas de uma dimensão coletiva que, embora não se amolde às categorias tradicionais do direito privado, é relevante para o direito contratual. Apresenta-se contribuição à identificação de vetores para o tratamento jurídico das redes.
Keywords: Commercial concession; Concessão comercial; Contractual networks; Contratos; Direito Comercial; Distribution; Franchise; Franquia; Interest of the network

La prueba en el proceso de consumidores y usuarios - Mollar Piquer, María Pilar (Universitat Jaume I, 2017)
El trabajo introduce la legislación básica de derecho de consumo, analiza los diferentes tipos de acciones que se pueden plantear y tras una mención al arbitraje y la mediación en los procesos de consumo, habla del procedimiento y se adentra en la prueba en el proceso para a continuación analizar la prueba específica a llevar a cabo en los procesos de consumo, tanto en relación a los medios, como al objeto de la prueba para que se pueda lograr una sentencia favorable al consumidor. Trata además la prueba en concretos procesos de consumo, como los de productos defectuosos, publicidad ilícita, competencia desleal, claúsulas abusivas o productos financieros, entre otros. Existe además una especialización en la prueba de consumo relativa a las presunciones y al recurso a la inversión de la carga de la prueba que también son objeto de análisis.
Publication Title: TDX (Tesis Doctorals en Xarxa)
Keywords: Administració i dret; Consumidores y usuarios; Consumo; Negocis; Pericial; Proceso consumidores; Productos defectuosos; Prueba

The regulation of unsolicited electronic communications (SPAM) in South Africa : a comparative study - Tladi, Sebolawe Erna Mokowadi (University of South Africa, 2017)
The practice of spamming (sending unsolicited electronic communications) has been dubbed “the scourge of the 21st century” affecting different stakeholders. This practice is also credited for not only disrupting electronic communications but also, it overloads electronic systems and creates unnecessary costs for those affected than the ones responsible for sending such communications. In trying to address this issue nations have implemented anti-spam laws to combat the scourge. South Africa not lagging behind, has put in place anti-spam provisions to deal with the scourge. The anti-spam provisions are scattered in pieces of legislation dealing with diverse issues including: consumer protection; direct marketing; credit laws; and electronic transactions and communications. In addition to these provisions, an Amendment Bill to one of these laws and two Bills covering cybercrimes and cyber-security issues have been published. In this thesis, a question is asked on whether the current fragmented anti-spam provisions are adequate in protecting consumers. Whether the overlaps between these pieces of legislation are competent to deal with the ever increasing threats on electronic communications at large. Finally, the question as to whether a multi-faceted approach, which includes a Model Law on spam would be a suitable starting point setting out requirements for the sending of unsolicited electronic communications can be sufficient in protecting consumers. And as spam is not only a national but also a global problem, South Africa needs to look at the option of entering into mutual agreements with other countries and organisations in order to combat spam at a global level.
Keywords: Anti-spam laws; Commercial electronic messages; Consumer law; Direct marketing; Electronic commerce; Electronic communications; Electronic mail (e-mail); International cooperation; Right of privacy; Spam (Electronic mail); Telemarketing; Unsolicited commercial communications; Unsolicited electronic communications

Le droit des pesticides au Bénin : conditions de mise sur le marché et la responsabilité des distributeurs - Bonou, Jeacques Gbenonman (Unievrsité Paris 13, 2017)
Le développement rapide de l’industrie chimique dans le monde et les risques insoupçonnables et souvent insidieux des produits chimiques ont permis à la communauté internationale de réglementer la commercialisation de ces produits. Ainsi, il a été élaboré des textes et des Conventions internationales réglementant le commerce de ces produits. L’objectif de la majorité de ces instruments est de favoriser le développement économique sans pour autant mettre à mal la santé publique et l’environnement. L’application de ces instruments internationaux a seulement atteint une maturité dans les pays industrialisés mais pose un véritable problème de société dans les pays en développement. L’effectivité de ces règles dans les pays en développement et principalement au Bénin est problématique. Les Etats se doivent de les ratifier ces instruments et de les transposer dans leurs législations nationales. Le législateur béninois a bien suivi cette démarche à travers la loi n°91-004 du 11 février 1991 portant réglementation phytosanitaire au Bénin et la loi-cadre sur l’environnement dont les dispositions sont applicables en matière de substances chimiques ou de pesticides. Ces différentes lois, ont-elles permis d’atteindre les objectifs de la protection agricole, de la santé publique, et de l’environnement ? Comment peut-on mettre en jeu la responsabilité des distributeurs béninois en cas de dommages liés à ces produits ? Les réponses à ces interrogations nous ont permis de constater des défaillances dans ces lois et que le législateur béninois doit moderniser sa législation dans le but de renforcer l’encadrement de ces produits. Quant aux mécanismes nationaux de responsabilité, la réforme à ce niveau est indispensable. Sinon les régimes de responsabilité ne permettent pas de responsabiliser les distributeurs. Les mécanismes de responsabilités existant dans le droit positif comportent des insuffisances pour une mise en œuvre efficace de la responsabilité des distributeurs. Ces insuffisances sont aussi bien réelles sur le plan de la responsabilité civile que pénal. Le législateur doit profondément revoir tout le dispositif applicable aux distributeurs, tout en modernisant le droit de la responsabilité civile avec la consécration de la responsabilité objective du fait des activités dangereuses. Aussi faudrait-il consacrer la responsabilité des personnes morales dans le droit pénal. The rapid development of the chemical industry in the world and the unsuspected and often insidious risks of chemicals have enabled the international community to regulate the marketing of these chemicals. For example, texts and international conventions regulating trade in these products have been developed. The majority of these instruments aim to promote economic development without undermining public health and the environment. The application of these international instruments has only reached maturity in the industrialized countries but poses a real societal problem in the developing countries. The effectiveness of these rules in developing countries, and especially in Benin, is problematic. States must ratify these instruments and transpose them into national legislation.The Beninese legislator has indeed followed this approach through Act No. 91-004 of 11 February 1991 on phytosanitary regulations in Benin and the framework law on the environment, the provisions of which apply to chemical substances or pesticides. Have these different laws made it possible to achieve the objectives of agricultural protection, public health and the environment? How can the Beninese distributors be held liable for damages related to these products? The answers to these questions allowed us to note deficiencies in these laws and that the Beninese legislator must modernize its legislation with the aim of reinforcing the supervision of these products. As for national accountability mechanisms, reform at this level is essential. Otherwise liability schemes do not allow distributors to be held accountable. The mechanisms of responsibility in the positive law contain inadequacies for an effective implementation of the responsibility of the distributors. These shortcomings are as real in terms of civil and criminal liability. The legislator must thoroughly review the entire system applicable to distributors, while modernizing the law of civil liability with the recognition of the objective liability for dangerous activities. Consequently, the liability of legal persons should be enshrined in criminal law.
Keywords: Bénin; Commerce produits chimiques; Industries chimiques; Legislation béninoise; Législation; Pays en voie de développement; Produits chimiques; Responsabilité (droit); Réglementation Phytosanitaire

L’obligation générale d’information du banquier à l’égard du client dans la zone U.E.M.O.A à la lumière du droit français - Dolo, Yamadou (Université Cheikh Anta Diop, 2017)
Keywords: Banquier; Client; Droit français; Information; UEMOA

Towards responsible lending in Namibian consumer credit law : a comparative investigation - Asheela, Ndatega Victoria (University of Pretoria, 2017)
The regulation of consumer credit in Namibia mainly is provided for by the Usury Act 73 of 1968 and the Credit Agreements Act 75 of 1980. These legislative enactments originated in South Africa and were applied in South West Africa during the period of South Africa’s mandate over what is now the Republic of Namibia. Despite the fact that these enactments are over 35 years old, they are substantially unchanged. In response to an awareness of the threat of consumer over-indebtedness and other events such as financial crises, the purpose in this thesis is to undertake a situational analysis of the debt prevention measures as provided for by the Namibian legislative framework and the extent of protection these measures afford consumers in terms of irresponsible credit and over-indebtedness. A broad survey of the policies aimed at promoting responsible lending benchmarks the Namibian consumer credit regulatory framework against the leading international best principles which have been developed in response to global economic challenges. The Namibia Financial Institutions Supervisory Authority in the 2014 Microlending Bill proposes to introduce responsible lending practices in the form of a compulsory pre-agreement assessment of the prospective consumer before providing them with credit. In a comparative investigation, the creditworthiness assessment and related measures central to the responsible lending regimes in South Africa and Australia are considered. Measuring the Namibian consumer credit regulatory framework against these recent developments, it is submitted that the current debt prevention measures are inadequate in protecting consumers from irresponsible credit lending and the risk of consumer over-indebtedness. This thesis supplies reasons for the need in Namibia to update the regulatory structure of the credit industry in order to protect consumers. As a contribution to the promotion of a culture of responsible lending in the Namibian consumer credit market, the thesis proposes the introduction of responsible lending measures in Namibia’s consumer credit legislative framework.
URI: https://repository.up.ac.za/handle/2263/65659
Keywords: Consumer credit; Debt; Namibia

Consumer arbitration in South Africa and its effect on the consumer's right to redress and enforcement - Rantsane, Ditaba Petrus (University of Pretoria, 2017)
The thesis entitled "Consumer arbitration in South Africa and its effect on the consumer‘s right to redress and enforcement" notes with concern the outdated and inadequate nature of the Arbitration law currently applied in South Africa. The fact that the Act was enacted in 1965 and has never been amended highlights the desperate need to review the prevailing arbitration law with a view to aligning it with the current needs of the business world. The thesis addresses the concern that consumers are not adequately protected by the current arbitration law and thus substantially develops the discourse on the topic of arbitration in situations of unequal bargaining power. It raises three primary research questions in this context. The first question reads thus, if private arbitration is properly conducted should it still provide the parties with the envisaged benefits? Secondly, is private arbitration constitutional, especially as it impacts upon consumers‘ contracting with large corporations? Thirdly, is the private arbitration process as it is currently applied, constitutional as far as it denies parties an appeal on merits against an award that is clearly wrong? The thesis attempts to answer these questions and offer recommendations for the South African Law Reform Commission (SALRC) within the specific context of commercial arbitration. In addressing these research questions, the thesis incorporates a brief overview followed by a detailed discussion of the Arbitration law framework in South Africa and abroad. The discussion of arbitration abroad is done in order to identify best practices, which could be adapted to suit the South African environment. International Arbitration law receives attention and a few observations regarding how selected foreign jurisdictions treat arbitration. Finally, the thesis explores the possibility of establishing an independent institution that will be fully equipped to handle arbitration proceedings from inception to completion.
URI: https://repository.up.ac.za/handle/2263/67886
Keywords: Consumer arbitration; Consumer rights

A proteção internacional do consumidor turista - Soares, Ardyllis Alves (Universidade Federal do Rio Grande do Sul, 2017)
Proteção internacional do consumidor turista. Primeiramente, são apresentados elementos para demonstrar a relevância e a contextualização do tema. Em seguida, são apresentados alguns conceitos importantes para delimitar o tema, seguido de uma descrição sobre o comportamento e as expectativas do consumidor turista. Na segunda parte, são apresentados os diferentes meios de tutela internacional do consumidor turista, começando pelas organizações internacional, passando pelos blocos regionais e concluindo com os desenvolvimentos nacionais. Na terceira parte, trata-se da governança global em prol da proteção internacional do consumidor. Começase pela governança local e a cooperação jurídica internacional; em seguida, é trabalhada a governança regional e a cooperação jurídica internacional, concluindo com a governança global e a cooperação jurídica internacional. Como conclusão, defende-se a inserção de proposta da regra mais favorável ao consumidor em casos internacionais na atualização do Código de Defesa do Consumidor; no âmbito regional, há uma demanda por aprimoramento e estruturação da tutela do consumidor turista internacional; Por fim, conclui-se da necessidade de uma proteção do consumidor turista internacional de forma mais difusa, por meio de uma convenção da Conferência de Haia sobre o Direito Internacional Privado - HCCH.
Keywords: Active consumer; Aktiv Verbraucher; Consumer; Cooperação internacional; Defesa do consumidor; Direito do consumidor; Intenational cooperation; International; Internationales Kooperation; Proteção ao consumidor; Tourist; Verbraucher

Problems regarding exemption clauses in consumer contracts : the search for equitable jurisprudence in the South African Constitutional realm - Tembe, Herman C. (University of Pretoria, 2017)
URI: https://repository.up.ac.za/handle/2263/65730
Keywords: Consumer contracts; Exemption clause; South Africa

Réflexions autour de la protection des consommateurs de la zone UEMOA dans sa perspective d'intégration économique communautaire : Étude comparative avec le droit europén (Français) - Zoungrana, Ibrahim (Université de Perpignan Via Domitia, 2016)
Depuis un certain nombre d’années, les Etats membres de l’UEMOA se sont lancés dans un vaste projet de libéralisation économique suivi d’une ambition d’intégration économique, rendant ainsi difficile les projets législatifs consuméristes nationaux. A ce titre, nous nous posons la question de savoir, si les ambitions de cette intégration économique prennent en compte l’intérêt des consommateurs et si elles ne se heurtent pas au besoin d’une protection efficace des consommateurs sur le marché commun. Comment concilier ce libéralisme économique avec une protection efficace des consommateurs au sein du marché commun ? Autrement-dit, une divergence entre les différentes dispositions des Etats membres ne serait-elle pas dommageable aux consommateurs ? Enfin, peut-on parler d’un véritable ordre juridique consumériste ouest-africain? Nous tentons de démontrer à travers cette étude qu'il y a un acquis de protection communautaire des consommateurs, mais que celle-ci est sectorielle. Toutefois, les domaines laissés vacants par le droit communautaire sont implicitement régis par les différentes dispositions nationales embryonnaires et plus ou moins identiques, d'où le risque d'insécurité juridique et la nécessité du projet OHADA sur le droit des contrats comme une perspective dans le cadre de la protection des consommateurs de l'UEMOA au sein du marché commun.
Keywords: Afrique occidentale; Consommateur (protection); Droit européen et français; Intégration économique; Protection des consommateurs; UEMOA; WAEMU

Contribution à l'étude des déterminants de la performance de l'entreprise : impact de la création de valeur pour le client sur la performance des entreprises hôtelières en Tunisie - Oubya, Ghozlene (Université Côte d'Azur, 2016)
Cette thèse avait pour objectif de contribuer à l’étude des déterminants de la performance de l’entreprise mesurée du point de vue client. Nous nous sommes intéressés à la création de valeur en général et à la création de valeur pour le client en particulier comme facteur explicatif de la performance de l’entreprise mesurée par la satisfaction et la fidélité du client. Au niveau de notre travail, nous avons pris le domaine du tourisme tunisien comme terrain de recherche et notre objectif à été d’étudier l’impact de la création de valeur pour le client sur la performance des hôtels tunisiens. Nous avons cherché à savoir si les services proposés par une entreprise hôtelière génèrent de la valeur pour ses clients et donc pour celle-ci.Au niveau empirique, l’intérêt de ce travail à été de rejoindre les préoccupations économiques du pays où plusieurs études tunisiennes (ONTT, ministère du tourisme) préconisent de créer plus de valeur pour les clients afin de relancer le secteur et améliorer la performance des entreprises hôtelière touristiques ; ainsi que les préoccupations des managers qui s’intéressent aux conditions appropriées pour atteindre la performance grâce à la création de valeur. This thesis aimed to contribute to the study of the determinants of business performance measured from the customer perspective. We are interested in value creation in general and to creating value for the customer in particular as an explanatory factor in the business performance measured by customer satisfaction and customer loyalty. In this research, we took the tunisian tourism as a research field and our objective was to study the impact of the value creation for the customer on the performance of the tunisian hotels. We investigated whether the services provided by hotel companies generate value for its customers and thus for the hotels. Empirically, the interest of this work was to join the economical concerns of the country where several Tunisian Studies (ONTT, Ministry of Tourism) call to create more value for customers in order to boost the sector and improve business performance of the hotels; and the concerns of managers who are interested in meeting the appropriate conditions to achieve performance through value creation.
Keywords: Companies; Consommateur (satisfaction); Création de valeur; Customer; Efficacité de l'organisation; Hôtels; Management de la performance; Productivité; Relations avec la clientèle; Relations clients-fournisseurs; Satisfaction client; Tunisie; Value creation

A critical review of the treatment of dominant firms in competition law : a comparative study - Munyai, Phumudzo S. (University of South Africa, 2016)
In South Africa compliance with competition law has become a major concern for firms that achieve and maintain certain levels of success and growth in the market, as their actions are often a source of complaints and litigation by rivals and competition authorities. With substantial financial penalties often levied against them for a variety of conduct deemed to constitute an abuse of their market position, dominant firms must constantly be aware of the likely impact of their business strategies and actions on both rivals and consumers. What were once thought to be normal and economically sound business practices and decisions, such as cutting prices to attract customers, have now acquired new meanings, with devastating consequences for dominant firms. So, are dominant firms under attack from competition law? In this study I aim to determine this. I track the historical development of competition law in three jurisdictions: South Africa, America, and the EU, with the aim of identifying traces, if any, of hostility towards dominant firms in the origins of competition law. I further investigate whether the formulation and enforcement of certain aspects of existing abuse of dominance provisions manifest as hostility towards dominant firms. While acknowledging the important role that competition law enforcement plays in promoting competition and enhancing consumer welfare, I conclude that significant unjustified economic and legal prejudice is suffered by dominant firms as a result of the way in which certain abuse of dominance provisions have been formulated and applied. I also offer appropriate recommendations.
Keywords: Abuse of dominance; Anti-monopoly; Anticompetitive effects; Anticompetitive harm; Antitrust law; Causation; Competencia; Competition Appeal Court; Competition Commission; Competition Tribunal; Competition law; Consumer harm; Consumer welfare; Counterfactual; Dominant firms; Exclusionary conduct; Hostility; Monopoly; Super-dominant; Unilateral conduct

Collective action in comparative and empirical perspective: towards a socio-legal theory - Fortes, Pedro Rubim Borges (University of Oxford, 2016)
This DPhil thesis enhances existing understandings of collective action through a comparative and empirical study. Empirical analysis of economic, political, juridical, and social dimensions of the Brazilian experience reveals that some central understandings in existing literature are not borne out in this empirical context. In particular, the assertion that low monetary incentives for individuals hinder growth in use of collective action is strongly challenged. The Brazilian experience is contextualised through comparative analysis of three legal traditions of collective action: class actions; collective redress; and civil public actions. The Brazilian system presents a setting with potential for regulatory enforcement of consumer protection law, but rare episodes of consumer compensation or the imposition of punitive damages on corporations. With low monetary incentives, the growth of collective actions is explained by non-monetary incentives and investment in social capital through development of institutional trust and legal institutions. Collective actors develop their organisational infrastructure and perform their roles as representatives through institutional dynamics of concentration, competition, cooperation, and deference. The coexistence of multiple institutional actors in the regulatory space reduces agenda control, increases opportunities for consumer participation, and increases oversight of regulatory capture. The categories of diffuse, collective, and homogeneous individual rights explain the role of law in establishing procedural pathways and special features. This study is broadened through analysis of the legal environment and the potential regulatory impact of collective actions on the social relationships between businesses and consumers. I also evaluate limitations and possibilities regarding access to justice, judicial economy, compensation, and deterrence. This thesis indicates the possibility of developing a socio-legal theory of collective action, which would enhance our understanding of the complex dynamics at play by going beyond analysis of the consumer experience as merely an economic transaction or a legal object, analysing them instead as a complex social relationship.
Keywords: Collective action; Consumer (protection); Consumer compensation; Droit de la consommation

The Regulation of Promotional Competitions in South Africa - Strachan, Daniel Petrus (University of Pretoria, 2016)
Promotional competitions are competitions in which prizes are awarded by lot or chance in order to promote goods or services. Due to the chance element, these competitions are often categorised as lotteries or gambling. Initially, South African legislation did not make provision for the running of promotional competitions, but this situation changed when the Lotteries Act, 1997 came into force. Currently, promotional competitions are regulated by the Consumer Protection Act, 2008 (CPA). This thesis examines the regulation of promotional competitions in South Africa. It commences with a background discussion, which touches on the relevant terminology and some sociological aspects. It then considers the consequences of gambling and the need for and nature of regulation, and deals with the marketing and consumer protection contexts. This is followed by a brief overview of the global and South African history of gambling, lotteries and promotional competitions, which includes a discussion of South African case law. Foreign law relating to promotional competitions in New Zealand and Great Britain is explored in order to compare this to the South African position. This is followed by an examination of the current regulation of promotional competitions in South Africa, including a discussion regarding the interplay between the CPA and the Lotteries Act and a detailed analysis of the CPA’s provisions. The self-regulation of promotional competitions is discussed as well. The concluding chapter of this thesis contains recommended solutions for the problems identified in the analysis of the relevant legislation.
URI: https://repository.up.ac.za/handle/2263/56056
Keywords: Competencia; Competition law; Concurrence (droit); Consumer law; Droit de la consommation

La réception par la jurisprudence de la législation sur le crédit à la consommation - Franc, Patricia (Université de Saint-Etienne, 2015)
Le consommateur, lorsqu’il souscrit un contrat de crédit pour les besoins de sa vie courante, achat d’une automobile par exemple, bénéficie d’un certain nombre de protections. Différentes sources du droit sont susceptibles d’être articulées : les mécanismes du droit commun des contrats présents dans le Code civil, mais aussi une législation spéciale, née de la loi dite SCRIVENER I du 10 janvier 1978, présente dans le Code de la consommation. Cette législation spéciale, bien que récente, a été modifiée à plusieurs reprises, la dernière modification d’importance étant la transposition en droit français de la directive européenne du 23 avril 2008 par la loi du 1er juillet 2010. Le droit du crédit à la consommation est un droit jeune, dense, foisonnant, ambitieux, qui revendique un haut degré de protection du consommateur et fait du formalisme son cheval de Troie. Mais c’est aussi un droit de passion, élaboré souvent dans l’urgence, sensible politiquement, médiatisé, objet de lobbies, parfois maladroitement rédigé ou transposé, approximatif, lacunaire. Au sein de la Cour de cassation, c’est à la Première Chambre civile qu’il appartient de connaître des questions en lien avec le droit de la consommation. Dès lors, comment la Première Chambre civile parvient-elle à manipuler ce droit spécial du crédit à la consommation ? Parvient-elle à en gommer les défauts, à en pallier les manques ? Comment articule-t-elle les protections en présence ? Doit-elle faire face à des résistances de la part des juridictions du fond ? Dans cette tâche unificatrice, le droit commun lui apporte-t-il un secours bienvenu ? Et la CJUE ? In fine, le consommateur emprunteur est-il protégé efficacement ?
Keywords: Code de la consommation; Consommateur (protection); Consumer credit; Consumer protection; Credit law; Crédit à la consommation; Droit commun; Loi Scrivener

Essai critique sur la protection du consentement de la partie faible en matière contractuelle - Maume, Florian (Université Evry-Val-d’Essonne, 2015)
La notion de « partie faible » n'est pas conceptualisée en droit français des contrats. Elle est pourtant fréquemment invoquée, au point d’avoir été à l'origine de la création de pans entiers du droit, comme le droit de la consommation. La situation est donc paradoxale. Par ailleurs, les protections du consentement de ces contractants présumés faibles sont multiples, éparpillées et souvent peu efficaces. Cette spécialisation extrême conduit même parfois à desservir la partie protégée. Aussi convient-il de conceptualiser la notion de partie faible, et par là même de clarifier la protection de son consentement. Ces créations doivent, au reste, être intégrées dans le Code civil, afin de constituer un véritable droit commun bénéficiant à tous, plutôt qu’une série d’exceptions ne profitant qu’à certains.
Keywords: Consentement (droit); Consommateur (protection); Contrats; Partie faible (droit); Vices du consentement

Engagement et désengagement contractuel, étude de droit de la consommation et de droit civil - Bideau, Clément Le (Université Grenoble Alpes, 2015)
L'engagement est au cœur du lien social, aussi les juristes lui ont accordé une place considérable au sein de la sphère du droit ; le droit des contrats est le premier concerné. A côté de cela, il n'est plus possible d'ignorer le phénomène du désengagement. La place croissante de ce dernier a conduit la doctrine à se pencher sur lui, à s'intéresser aux règles qui prévoient en matière de droit des contrats une faculté de repentir. Compte tenu de cela, il nous paraît particulièrement intéressant de traiter de l' « engagement », en le confrontant avec son symétrique, le « désengagement ». Cela pourrait, croyons-nous, changer la façon dont l'un et l'autre peuvent être appréhendés. Et nous avons choisi de concentrer nos efforts sur les dispositifs issus du droit de la consommation, qui à nos yeux sont l'expression la plus forte de l'idée de désengagement contractuel. On one hand, the commitment is at the heart of the social link, therefore the civil lawyers granted it a crucial place within the sphere of the law. It is particularly true for contract law. On the other hand, it is not possible any more to ignore the phenomenon of the right of withdrawal. The increasing place of the latter, led the doctrine to deal with it, to be interested in the rules, which plan regarding contract law a faculty to regret. Considering it, it seems to us particularly interesting to deal with the "commitment", by confronting it with its contrary, the "right of withdrawal". It could, we believe, change the way both can be apprehended. Therefore, we focus on the consumer law, which is, for us, the highest expression of the right of withdrawal.
Keywords: Contract law; Contrats de consommation; Désengagement; Force obligatoire; Irrévocabilité; Repentir; Right of cancellation; Right of withdrawal; Rétractation

Le droit à l'interopérabilité : études de droit de la consommation - Duponchelle, Marie (Université Paris 1, 2015)
L'interopérabilité devrait être officiellement reconnue, aujourd'hui, comme un droit du consommateur : elle répond à ses besoins de maîtriser ses données, ainsi que d'interconnecter ses outils numériques. Ce droit devrait être opposable aux sujets passifs que sont les éditeurs de logiciels et de contenus numériques. Cependant, le corpus juridique actuel, comprenant essentiellement une obligation d'information précontractuelle et une obligation de ne pas faire obstacle à l'interopérabilité, ne permet pas la mise en œuvre effective de ce droit. Il semble donc nécessaire de formuler des propositions de révision des textes existants, dans la préservation d'un équilibre avec la protection du droit d'auteur et des droits voisins. En premier lieu, s'agissant de l'obligation d'information, les modifications doivent viser à la systématisation de l'information précontractuelle relativement à l'interopérabilité logicielle, à la charge des sujets passifs du droit. En second lieu, s'agissant de l'obligation de ne pas faire obstacle à l'interopérabilité, les propositions doivent avoir pour objet l'instauration d'une réelle obligation de faire, relativement à la mise en œuvre de l'interopérabilité, ce selon deux axes : une obligation de recourir à un format ouvert et non protégé de données ; l'établissement d'une responsabilité de plein droit concernant cette obligation de mise en œuvre effective de l'interopérabilité.
Keywords: Consommateur; Consommateur (protection); Consumers; DRM; Droit d'auteur et informatique; Interconnexion de réseaux (télécommunications) – Droit; Interoperability; Intéropérabilité; Mesures techniques de protection

Relevé d'office du juge et droit de la consommation - Gillotot, Annelieke (Université d'Avignon, 2014)
L’office du juge est organisé par le Code de procédure civile au sein des principes directeurs : le juge est tenu de trancher le litige en droit et qu’il dispose, pour ce faire, de la faculté du relevé d’office de moyens de droit. Cette mission soulève une difficulté particulière en droit de la consommation, et notamment au regard du droit des clauses abusives et du crédit à la consommation : ces domaines impliquent la prise en compte du déséquilibre contractuel dû à la faiblesse du consommateur. L’office du juge est confronté à la nécessité de protéger cette « partie faible », ce qui pose la question de savoir si le juge dispose ou non de la faculté du relevé d’office. La difficulté de la réponse à y apporter ouvre une riche controverse (Partie 1) ; le législateur, au gré des réformes, et le juge, au gré des revirements, vont enrichir cette dernière pour finalement aboutir à une consécration du relevé d’office du juge (Partie 2).Le juge national avait d’abord clairement désapprouvé l’exercice du relevé d’office au nom de la notion d’ordre public de protection. La controverse était finalement soumise à l’appréciation du juge communautaire qui avait permis une consécration de la faculté du relevé d’office. Poussé par la jurisprudence communautaire, le législateur français avait fini par s’aligner sur cette exigence. Puis c’est une nouvelle impulsion de la jurisprudence communautaire qui va à nouveau remettre en cause le droit interne par la consécration d’une obligation du relevé d’office pour le juge. La nouvelle loi « Hamon » du 17 mars 2014 et la jurisprudence interne récente ne témoignent pas d’une réelle satisfaction des exigences posées par le droit communautaire.Il faut saisir, de l’ensemble de cette construction laborieuse de la jurisprudence et de la législation interne, la difficulté que pose la question du relevé d’office du juge en droit de la consommation, qui appelle de prochaines évolutions.
Keywords: Clause abusive; Consommateur; Consommateur (protection); Crédit à la consommation; Droit de la consommation; Moyen relevé d’office; Office du juge; Ordre public de protection

Les mesures de prévention du surendettement des particuliers : à la croisée des chemins des droits commun et spécial - Loyer, Clémentine (Université de La Rochelle, 2014)
De création récente, la législation sur le surendettement a toujours eu pour ambition de prévenir et de traiter les situations de surendettement des particuliers. Présenté à son origine comme le droit « de ne pas payer ses dettes », le droit du surendettement a été intégré au Code de la consommation. Essentiellement envisagées comme la conséquence d’une consommation s’exerçant à crédit, les mesures préventives ont, de ce fait, été développées dans le cadre des règles de formation et d’exécution des contrats de crédit et de cautionnement. Face aux insuffisances de cette réglementation préventive, le droit commun des obligations est, à son tour, venu édicter des règles en vue de pallier les lacunes des mesures légales. Malgré les bénéfices apportés par la jurisprudence, l’efficacité de la prévention reste toutefois relative. En effet, tant la difficile conciliation des sources préventives que l’approche restrictive qui est envisagée du phénomène, mettent un frein à l’élaboration d’une prévention efficace. C’est au travers des règles de procédure de traitement du surendettement mais également, dans la redéfinition des notions d’endettement et de la personne vulnérable face au risque de surendettement, que les réponses à une prévention plus efficiente apparaissent. Recently created the overindebtedness legislation has always aimed to prevent and cure individual indebtedness situations. To his origin as the “right not to pay its debts” the indebtedness law has been integrated into the French consumer Code. Essentially seen as a consequence of consumption exerted on credit, preventive measures have been developed in the framework of the rules of formation and execution of credit agreements and surety. Given the inadequacies of this preventive legislation, the common law of contract is, in turn, came to make rules for any shortcomings of legal action. Despite the benefits of the law, the effectiveness of prevention, however, is relative. Indeed, as the difficulty of reconciling preventive sources that the restrictive approach proposed of the phenomenon, have no benefit on the development of effective prevention. It is through procedural overindebtedness rules but also in redefining the concepts of debt and the vulnerable person to the risk of debt distress, that the answers to more efficient prevention appear.
Issue: 2014LAROD004
Keywords: Cautionnement; Consommateur (protection); Consommation (droit); Contract; Credit; Creditor; Créancier; Crédit; Crédit à la consommation; Debtor; Débiteur; Obligation; Overindebtedness; Prevention; Prévention; Surendettement

Le référencement : contribution à l'étude de la nature juridique d'un contrat majeur de la grande distribution - Vallas, Philippe (Université de Strasbourg, 2014)
Le référencement est la technique contractuelle d'approvisionnement majeure de "la grande distribution". Apparue dans les années 70, elle partage son nom avec une pratique du "e-commerce" avec laquelle elle n'a, pourtant, aucun rapport. C’est un mode de regroupement de la puissance d'achat, reconnu par un arrêt du Tribunal de Grande Instance de Strasbourg du 29 septembre 1983 comme une relation tripartite, dans laquelle la structure de regroupement (référenceur) en vertu d'un "contrat d'affiliation" ou "de groupement" négocie des conditions de ventes, dans un "contrat de référencement" avec les fournisseurs, dont ses membres (distributeurs) pourront directement se prévaloir pour conclure des contrats "d'achat/vente". Ces différentes phases sont liées, ce qui en fait un "contrat complexe" et "sui generis". Elle se révèle polymorphe, ce qui a donné lieu à de multiples hypothèses fonctionnelles : contrat unilatéral, mandat, contrat de commission, courtage, stipulation pour autrui, et ses effets peuvent impacter l'ordre public économique. A l’étude, règles contractuelles et règles de concurrences interagissent entre elles au détriment d'une nécessaire sécurité juridique, d'où la recherche d'éléments sur lesquels bâtir un régime stable. On les trouve dans la "globalisation des avantages", formant la cause du référencement, et la "commission de gestion", qui forme celle de l’intervention du référenceur. La confrontation de leurs conditions de validité aux hypothèses émises se révélant peu satisfaisante, nécessite de s'orienter vers une approche sociétaire du problème, seule à même de répondre, valablement, à la question de la nature du référencement et de son régime juridique.
Keywords: Agency fees; Agent; Brokerage; Centrales d'achats; Commission; Contrats innommés; Courtage; Gestion de l'approvisionnement; Globalisation; Mandat; Mondialisation – Influence; Prime; Society; Société; Stipulation; Sui-generis

The impact of the unfair commercial practices directive (2005/29/EC) on contract law - Đurović, Mateja (European University Institute, 2014)
This thesis examines the relationship between the law on unfair commercial practices and consumer contract law. The thesis develops the claim that Directive 2005/29/EC, on unfair commercial practices (UCPD) has had a strong impact on the content of consumer contract law, despite the declaration concerning the independence between both branches of law contained in Article 3(2) UCPD. In order to substantiate this claim, the thesis examines the implications for consumer contract law of the main components of the regulatory regime laid down by the UCPD, namely, (1) the notion of average consumer, (2) the duty to trade fairly, (3) the duty of information and (4) the remedies. By looking both at the theoretical underpinnings and at the actual operation of this regulatory regime, the thesis casts light on the way in which the UCPD has shaped consumer contract law. The thesis further shows that this is an ongoing phenomenon whose ramifications may be far-reaching, for it implies that the UCPD is powerfully fuelling the Europeanization of contract law.
Accepted: 2015-02-09T12:46:29Z
Keywords: Consumer protection; Contracts; European Union countries

The action for injunction in EU consumer law - Ogorzałek, Magdalena (European University Institute, 2014)
In 1998 the European Union adopted a new self-standing instrument of collective enforcement - the Action for Injunction. Until then, the main focus was on the improvement of the position of the individual consumer through the adoption of substantive consumer law directives. The Injunction Directive provides for a general framework on consumer law enforcement in national and cross-border litigation. Qualified entities, public agencies and/or consumer organisations, are granted legal standing. National courts are bound to mutually respect the standing of EU wide registered qualified entities. Outside these clear-cut rules on the mutual recognition of standing, the Injunction Directive remains largely silent. The implementation into 28 Member States swiftly revealed the rather limited harmonising effect. The thesis investigates and explains how despite the legally approved diversity, the Injunction Directive contains the potential to turn diversity into convergence. The key to understanding the potential is the thesis of dualism of enforcement measures. Read together with the Annex the Injunction Directive establishes the deep interconnection between collective and individual enforcement, of substantive and procedural enforcement, of judicial and administrative enforcement. The different levels and means of enforcement should not be regarded separately but should always be looked at in their interplay, in their mutual institutional design and their mutual impact. Evidence for convergence can be found in the Invitel judgment of the ECJ and in the practice of consumer organisations via co-ordination actions across borders by which they overcome the boundaries of collective vs. individual or judicial vs. administrative enforcement. Regulation 2006/2004 re-adjusts the dualistic structure of enforcement in favour of public bodies and promotes convergence through para-legal means, through new modes of enforcement, through co-operation and co-ordination outside courts and in open interaction between administrative bodies, to which consumer organisations are admitted on approval only.
Accepted: 2015-02-09T14:17:54Z
Keywords: Consumer protection; European Union countries; Injunctions

The influence of the Consumer Protection Act 68 of 2008 on the common law of sale - Barnard, Jacolien (University of Pretoria, 2013)
The purpose of this thesis is to investigate to what extent the Consumer Protection Act 68 of 2008 (CPA) influences the common law of sale in South Africa. “Common law of sale” refers to the essentialia of sale (the minimum characteristics that parties must have consensus on to conclude a valid sale). The parties must have consensus on the intention to buy and sell, the things sold and the purchase price. The common law of sale also refers to the common law duties of the parties, the duties of the seller in particular (conversely therefore the rights of the buyer). The primary duties of the seller which will be investigated are: a. the duty of safe-keeping (including and investigation into the passing of benefit and risk doctrine); b. the duty of delivery and transfer of ownership; c. the warranty against eviction; and d. the warranty against latent defects. The primary common law duties of the buyer to pay the purchase price and accept the thing sold are included in the investigation as well. The formalities required in certain sale agreements, that wording must be in plain language as well as the buyer’s cooling-off rights are also investigated. An investigation into the influence of the CPA on the common law of sale in South Africa warrants a systematic framework and modus operandi which are: a. an investigation into the historical background of the common law of sale and its principles in the Roman law and Roman-Dutch law; b. a critical analysis of the position where the CPA is not applicable (the common law position); c. an extensive analysis and critical evaluation of the relevant provisions of the CPA and the influence thereof on the common law of sale; d. a comparative analysis of the appropriate provisions in Scotland and Belgium; e. a conclusion of the influence of the CPA on the common law of sale (whether the particular common law of sale principle is confirmed, amended or excluded in terms of the Act); and f. recommendations (taking into account the comparative analysis) regarding the rectification of uncertainties and ambiguities that arose as a result of the investigation. It is also important to remember that the existing principles of the common law of sale will still be applicable for transactions and agreements which fall outside the application of the Act. The golden rule to keep in mind when investigating the influence of the CPA on the common law of sale is to determine which approach and interpretation will be most beneficial to the consumer.
https://repository.up.ac.za/handle/2263/32798
Keywords: Common law of sale; Consumer Protection Act; South Africa

The concept ‘fairness’ in the regulation of contracts under the Consumer Protection Act 68 of 2008 - Stoop, Philip Nicolaas (University of South Africa, 2013)
The thesis analyses the concept ‘fairness’ in consumer contracts regulated by the Consumer Protection Act 68 of 2008, mainly from the perspective of a freedom and fairness orientation. It discusses the evolution of ‘fairness’ as background to a more detailed discussion of the classification of fairness into substantive and procedural fairness. The thesis examines dimensions of fairness, factors which play a role in the determination of fairness, and fairness- oriented approaches in an attempt to formulate a framework for fairness in consumer contracts. The main aspects that should be taken into account to justify a finding of fairness, or to determine whether a contract is fair, are identified. This analysis addresses, too, the extent to which the fairness provisions of the Consumer Protection Act are appropriate (with reference to the law of South Africa, Europe, and England).
Keywords: Consumer contracts; Consumer protection law; Contracts; Contractual fairness; Freedom of contract; Law of contract; Liberty of contract; Procedural fairness; Standardized terms of contract; Substantial fairness

A Proposed discharge dispensation for consumer debtors in Tanzania - Maghembe, Ngwaru Jumanne (University of Pretoria, 2013)
The Tanzanian private sector is growing, partly due to the state’s efforts to conform to the global economy. As the economy expands and the National Microfinance Policy of 2001 is realised, more and more credit has been made available to consumers. As a direct consequence of the increase of credit, the number of over- indebted consumers in Tanzania is on the rise. The current debt relief system is regulated by the Tanzanian Bankruptcy Act no. 9 of 1930, a piece of colonial legislation. Unfortunately this law is ineffective, costly and outdated. Some of the problems identified in this study with this debt relief regime include the lack of a cost- effective alternative to bankruptcy and its total reliance on the judiciary, an institution that is itself overburdened and requires reform. The purpose of this study is to make recommendations for the reform of the current debt relief system and propose a debt relief dispensation for consumer debtors in Tanzania that will efficiently cure over- indebtedness. A wide comparative investigation was undertaken in this study of selected common law, civil and mixed legal systems that have substantial experience with the boom in over-indebted consumers now facing Tanzania. A number of solutions were borrowed from these systems that may potentially solve Tanzania’s debt relief problem. One of the main findings of this thesis is that, over time, developed jurisdictions that rely on credit in the private sector appear to be converging on the same type of procedures and moderate philosophies for consumer debt relief. These include less judicial supervision for debt relief procedures, less freedom of choice for over-indebted consumers when it comes to the type of procedures available, and mandatory surplus income repayments for debtors who can afford it. In order to address the problems of the Tanzanian debt relief system, this thesis proposes a complete overhaul of the administration of debt relief procedures in Tanzania and the introduction of a combined alternative to bankruptcy that consists of three joint procedures. A number of amendments are also proposed for the Bankruptcy Act no.9 of 1930. This thesis states the status of legal developments as they were in the selected jurisdictions on 31 December 2012.
https://repository.up.ac.za/handle/2263/32961
Keywords: Bankruptcy Act; Current debt relief system; Tanzania

La protection du consommateur des services bancaires et des services d'assurance - Hammoud, May (Université Paris 2, 2012)
Une des conséquences de la crise économique et financière de 2008 réside dans des tentations incessantes et continues de récupérer la confiance ébranlée du consommateur vis-à-vis des professionnels du secteur des services financiers. Alors que la protection du consommateur constitue un thème fréquent en droit français -et récent en droit libanais- une telle recherche fait défaut en matière spécifique aux services bancaires et aux services des assurances en droit comparé. En effet, le sujet est souvent présenté sous des angles séparés de la protection du consommateur dans chacun des deux services, dans chacun des deux droits. Il en découle qu’un approfondissement global, mais non exhaustif, sur « la protection du consommateur des services bancaires et des services d’assurance » dans une perspective comparative entre les deux droits, français et libanais, nous permettrait de mieux connaître les caractéristiques d’une telle combinaison. Ainsi, une série de questions se pose : Quels sont les contours des protections octroyées à ces consommateurs ? Comment leurs intérêts collectifs et individuels sont-ils défendus par les gouvernements, les législateurs, les juges, et la société civile ? Quelles sont les conséquences juridiques d’une telle protection qui s’avère être parfois « irrationnelle » ? Cette recherche a donc pour finalité de tenter de répondre à toutes ces questions, à travers deux parties. Dans la première, il s’agit d’analyser la protection octroyée aux intérêts collectifs et individuels des consommateurs des services bancaires et d’assurance. Dans la seconde, l’attention sera portée sur la mise en oeuvre d’une protection curative, parfois « déraisonnable » des consommateurs des services bancaires et d’assurance.
Keywords: Assurance; Banking services; Banques; Consommateur; Consommateur (protection); Consumer; Droit français; Droit libanais; France; French law; Insurance services; Lebanese law; Lebanon; Liban; Professionals; Professionnels; Protection; Services bancaires; Services d'assurance; Études comparatives

La sanction de la violation du droit de la consommation dans les contrats de consommation - Douche-Doyette, Nathalie (Université de Lorraine, 2012)
La seconde moitié du XXème siècle a été marquée par l'avènement de la sociétéde consommation et, corrélativement, par l'apparition d'un droit nouveau dont l'objectif est de protéger les consommateurs : le droit de la consommation. Il se définit par sa finalité comme l'ensemble des règles dont l'objet est de protéger les intérêts des consommateurs et s'applique essentiellement dans les contrats de consommation. Aucun régime général de la sanction de la violation des dispositions consuméristes n'a été organisé par le législateur. Les sanctions prévues sont majoritairement des sanctions pénales, les sanctions civiles sont alors celles du droit commun des contrats.A partir du droit positif, l'étude cherche à construire un régime spécial de la sanction, commun à tous les contrats de consommation. L'étude est orientée vers la recherche de sanctions efficaces, qui permettent de renforcer l'effectivité de la règle de droit et la protection des consommateurs. Elle distingue nécessairement l' analyse de l'efficacité de la fonction réparatrice de la sanction, qui est conditionnée par la prise en compte de la situation de la victime du comportement sanctionné, et l'analyse de l'efficacité de la fonction dissuasive de la sanction qui est conditionnée par la prise en compte de la situation de l'auteur du comportement sanctionné.
Keywords: ABUSIVE CLAUSES; Clauses abusives; Concurrence déloyale; Consommateur (protection); Consumer contract; Consumer law; Contract interpretation; Sanctions; Contrats de consommation; Droit de la consommation; Interprétation des contrats; Lésion; Nullity of contracts; Nullité du contrat; Peines; Peines privées; Pratiques commerciales déloyales; Prejudice (resulting from a contractualimbalance); Protection des consommateurs; Protection of consumers; Sanctions; Unfair commercial practices

Les normes privées relatives à la qualité des produits : étude d’un phénomène juridique transnational - Sarrouf, Muriel (Université Paris 2, 2012)
Les normes privées intéressent le droit international à un double titre : se développant en marge du système interétatique classique, elles constituent l’un des visages d’une régulation privée transnationale émergente et soulèvent la question théorique de leur statut en droit international. Par ailleurs, leurs effets sur le commerce international (et particulièrement le fait qu’elles constituent un obstacle aux exportations des PED vers les marchés occidentaux), conduisent à s’interroger sur l’opportunité et les modalités de leur réglementation par le droit international des échanges. En dépit de leur diversité empirique qui rend difficile toute tentative de systématisation et de qualification juridique, nous considérons que la qualité des produits, qui constitue le fondement téléologique commun des normes privées, permet d’en justifier l’unité théorique et de les considérer comme un phénomène juridique à part entière. Nous démontrerons que les normes privées sont l’une des manifestations d’un droit transnational se développant en parallèle du droit interétatique « classique » et qu’elles jouissent par conséquent d’un statut juridique propre. De ce fait, leurs rapports avec la branche du droit international qu’elles intéressent le plus directement, le droit international des échanges, ne peuvent se limiter à l’approche classique de réglementation (ou approche « répressive », en ce qu’elle a pour seul but d’en limiter les effets restrictifs pour le commerce) mais doivent se concevoir dans une optique de coordination. The recent proliferation of private standards is not only of growing interest to economists who seek to evaluate its impact on trade flows; it is also relevant to international law, particularly to international economic law, in a double perspective. First, from the perspective of legal theory, the legal status of private standards has still to be determined. Second, from an empirical standpoint, private standards have the potential to negatively impact the access of developing countries to the markets of developed countries. This raises the question of the opportunity and modalities of submitting them to the disciplines of the WTO Agreements. This study demonstrates that private standards are one of the expressions of broader ‘transnational law’, a body of law that has been developing in parallel to ‘traditional’ state-centered international law. This implies that international law cannot merely consider private standards as an object to be disciplined; rather, the traditional ‘repressive’ approach should be rejected in favor of a more collaborative approach stressing the interrelations between the two bodies of norms as well as possible forms of coordination.
Keywords: Droit commercial (droit international); Droit transnational; Legal pluralism; Normes privées; OMC; Pluralisme juridique; Private standards; Qualité des produits; Transnational law; WTO

Le droit alimentaire européen dans les échanges commerciaux entre l'Union européenne et les pays subsahariens - Nyama, Annie Laurence (Université Montpellier 1, 2012)
Les échanges commerciaux de denrées alimentaires entre l'Union européenne et les Etats Subsahariens sont en constante augmentation et sont encadrés par les grands principes du droit alimentaire européen, composante du droit de la consommation. Ces grands principes énoncent des règles d'information des consommateurs, de sécurité, de conformité et de traçabilité des produits alimentaires qui doivent être respectés par toutes les parties prenantes du secteur agroalimentaire et des ses filières. C'est donc une masse importante de règles internationales, communautaires européennes qui se combinent aux textes nationaux. Les exportateurs / importateurs au sein de la Communauté, et les professionnels des pays tiers, mettent en œuvre ces règles dans les contrats de vente internationales des denrées. Les problèmes de santé et de sécurité sont posés par les consommateurs inquiets de leur protection. Mais les producteurs seront attentifs à l'évolution des règles qui protègent les consommateurs car elles conditionnent les activités de production, de transformation de transport, de stockage et de commercialisation. Certes, l'Afrique subsaharienne occupe une place faible dans le commerce mondial, mais son importance dans les échanges avec le continent européen, reste un facteur d'encouragement de la production des produits africains commercialisables. A cet effet, les pays subsahariens ne peuvent plus se contenter d'une réglementation locale, inadaptée, bien lacunaire et peu effective, au regard de l'importance des solutions aux questions sanitaires alimentaires dans le cadre du commerce mondial. D'ailleurs les importateurs européens imposent, contractuellement, à leurs partenaires africains le respect des impératifs sanitaires européens sans lesquels ils ne pourraient mettre les aliments importés en circulation en Europe. La thèse met en évidence un impératif de modernisation des instruments juridiques et institutionnels en Afrique subsaharienne. La place que prennent désormais les normes, quelles qu'en soient les différentes variantes est, à cet égard, très instructive. Les normes permettent aux producteurs et exportateurs des pays en développement de raccourcir les opérations complexes de compréhension des textes impératifs et des principes techniques et managériaux très modernes.
Keywords: Commerce international; Consumer law; Droit alimentaire européen; Droit de la consommation; Echanges Nord-Sud; European food law; International Trade; North-South trade; Sanitary food safety; Sécurité sanitaire alimentaire

La protection contre les clauses abusives du contrat d'assurance - Alkhalfan, Ismail (Université Montpellier 1, 2012)
Le contrat d'assurance est souvent donné comme un exemple du contrat d'adhésion. En fait, le contrat a été auparavant ; élaboré, rédigé, imprimé par l'assureur. Quant à l'assuré, il ne fait par la suite qu'adhérer à un contrat préétabli dont il n'a pas discuté les conditions. Il est donc nécessaire de protéger cet assuré contre les clauses abusives figurant dans son contrat. La protection contre les clauses abusives du contrat d'assurance provient de plusieurs sources. La source principale est le droit de la consommation et plus précisément l'article L. 132-1 du Code de la consommation. Cet article ne protège que l'assuré consommateur ou non professionnel. Quant aux autres sources, elles se trouvent dans le droit commun des contrats et les droits spéciaux applicables au contrat d'assurance. Si dans l'état actuel des textes, ces sources ne parlent pas d'une protection contre les clauses abusives stricto sensu, une proposition formulée en vue d'une réforme du droit des contrats, pourrait insérer une telle protection. Dans notre étude, nous analysons les différentes sources de la protection, en droit positif et droit prospectif, puis nous essayerons de proposer un texte qui garantira, à nos yeux, la meilleure protection de l'assuré contre les clauses abusives.
Keywords: Assurance; Clauses abusives; Consommateur (protection); Contrat d'assurance; Contrats d'adhésion; Insurance contract; Polices; Protection de l'assuré; Protection of insured; Unfair terms